2015
DOI: 10.1038/bjc.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate kinase-1 is a predictor of poor survival and a novel prognostic biomarker of chemoresistance to paclitaxel treatment in breast cancer

Abstract: Background:Phosphoglycerate kinase-1 (PGK1) has been recently documented in various malignancies; however, the molecular mechanisms of the variable PGK1 expression and its clinical significance in terms of survival status remain unclear.Methods:Real-time quantitative PCR (real-time qPCR) and western blotting were used to verify PGK1 expression in 46 fresh breast cancer tissues and matched normal tissues. A tissue microarray (TMA) comprising 401 breast cancer tissues and 123 matched normal tissues was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 39 publications
3
68
1
1
Order By: Relevance
“…PGK1 is also believed to participate in tumorigenesis, autophagy, and cancer metastasis . As a predictor of poor survival and a prognostic biomarker of resistance to chemotherapeutics, PGK1 is overexpressed in many malignancies, including breast cancer, liver cancer, and gastric cancer . Recent research has demonstrated that hypoxic stress, EGFR activation, or the expression of K‐Ras G12V or B‐Raf V600E results in the ERK1/2‐dependent phosphorylation of PGK1 at S203, leading to PIN1‐dependent PGK1 cis – trans isomerization, the binding of PGK1 to the TOM complex, and subsequently the mitochondrial translocation of PGK1 …”
Section: Discussionmentioning
confidence: 99%
“…PGK1 is also believed to participate in tumorigenesis, autophagy, and cancer metastasis . As a predictor of poor survival and a prognostic biomarker of resistance to chemotherapeutics, PGK1 is overexpressed in many malignancies, including breast cancer, liver cancer, and gastric cancer . Recent research has demonstrated that hypoxic stress, EGFR activation, or the expression of K‐Ras G12V or B‐Raf V600E results in the ERK1/2‐dependent phosphorylation of PGK1 at S203, leading to PIN1‐dependent PGK1 cis – trans isomerization, the binding of PGK1 to the TOM complex, and subsequently the mitochondrial translocation of PGK1 …”
Section: Discussionmentioning
confidence: 99%
“…In our surgical samples we have identified three distinct isoforms of PGK1 all increased with respect to the normal tissues. Many types of cancers, including those of the breast [47], the colon [48], the liver [49] and others, have been shown to exhibit an increased expression of PGK1. Indeed, it has been demonstrated that, in addition to its role as a glycolytic enzyme, PGK1 may act as a promoter of cancer progression and induce chemoresistance for some type of drugs [47,48].…”
Section: Phosphoglycerate Kinase 1 Pgk1 (Pgk1)mentioning
confidence: 99%
“…317/624 kinases were shown to correlate with survival in at least two cancers (Figure 3B). The kinases with the highest survival scores have been well described in the literature as predictive and prognostic biomarkers in multiple cancers; notably PGK1, PLK1 , and AURKA [49-51] . Less studied kinases such as ALPK3 (Tdark) (Figure S4) and SPEG (Tbio) also were shown to correlate with survival in 6 cancer cohorts (Supplemental table 4).…”
Section: Resultsmentioning
confidence: 99%